Punishing and rewarding: How do policy measures affect crop straw use by farmers? An empirical analysis of Jiangsu Province of China. (November 2019) - Sun, Dingqiang; Ge, Yang; Zhou, Yingheng
Abstract: Crop straw is the most important source of domestic energy in rural areas of many developing countries. However, as household income grows, rural residents begin to disuse crop straw, leading to a serious pollution and waste of biomass resources. This paper empirically examines the effect of public policy on crop straw use in the case of Jiangsu Province of China. Policy measures, such as burning ban and incentive programs for comprehensive use of crop straw, have important implication for rural energy supply and sustainable development of agriculture. Our results show that the burning ban has reduced crop straw burning in open field dramatically and driven farmers to retain straw into soil in sample areas. Straw retention subsidy, however, seems to play an insignificant role as the subsidy was low and not directly delivered to farmers. Moreover, crop straw markets in Jiangsu are inactive due partially to high cost of collecting and transporting crop straw, which may impose a big chanellge for straw-based energy plants that require larger scale and stable supply of crop straw. Our findings provide critical knowledge on designing and reforming current programs for crop straw management. Highlights: The paper studies the effect of public measures on the use of crop straw in China. Burning ban reduced straw burning in open fields and led to retention in the soil. Straw retention subsidy seems to play an insignificant role. Crop straw markets in rural China are inactive due to high transaction costs.